2018
DOI: 10.1103/physrevlett.121.171602
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Multiflavor Galileon-Like Theories

Abstract: We use Lie-algebraic arguments to classify Lorentz-invariant theories of massless interacting scalars that feature coordinate-dependent redundant symmetries of the Galileon type. We show that such theories are determined, up to a set of low-energy effective couplings, by specifying an affine representation of the Lie algebra of physical, non-redundant internal symmetries and an invariant metric on its target space. This creates an infinite catalog of theories relevant for both cosmology and high-energy physics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(81 citation statements)
references
References 54 publications
4
77
0
Order By: Relevance
“…The Jacobi identity (P, P, G) imposes [P, K] ∝ D + M for the vector inessential K of the dilaton D. This means that K necessarily generates a type of special conformal transformation. Because the case Z max = 1 without the dilaton was considered in [10,11], we will focus on what changes when the dilaton is included. We define our generators as follows: the scalar generator D is the dilaton.…”
Section: Multiple Scalar Goldstonesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Jacobi identity (P, P, G) imposes [P, K] ∝ D + M for the vector inessential K of the dilaton D. This means that K necessarily generates a type of special conformal transformation. Because the case Z max = 1 without the dilaton was considered in [10,11], we will focus on what changes when the dilaton is included. We define our generators as follows: the scalar generator D is the dilaton.…”
Section: Multiple Scalar Goldstonesmentioning
confidence: 99%
“…Recently, much effort has been devoted to classifying EFTs using both on-shell methods [1] (constructing amplitudes using minimal assumptions, see e.g. [2][3][4][5][6][7][8][9] and references therein), and Lie-algebras (classifying the algebras that dictate the structure of these amplitudes [10][11][12]). Both approaches are completely insensitive to the Lagrangian basis for the Goldstone self-interactions and hence avoid Lagrangian redundancies associated with non-linear field redefinitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can therefore ask which Lie-algebras are consistent within the framework of the coset construction for non-linear realisations [19][20][21] augmented with the crucial inverse Higgs phenomenon 3 [22]. For scalar EFTs Lie-algebraic approaches have been presented in [23,24] while in [25] these methods were used to prove that a gauge vector cannot be a Goldstone mode of a spontaneously broken space-time symmetry without introducing new degrees of freedom. This implies that the Born-Infeld (BI) vector is not special from the perspective of non-linear symmetries and enhanced soft limits (the same result was found in [8] where it was shown that the BI vector has a vanishing soft weight).Recently, we presented an algorithm for an exhaustive classification of the possible algebras which can be non-linearly realised on a set of Goldstone modes with linearly realised Poincaré symmetries 4 and canonical propagators in [26].…”
mentioning
confidence: 99%
“…This algebra also appeared in[24] and let us note that it is not clear if there exists a sensible realisation where both scalars have canonical kinetic terms. However, we will see in a moment that even if this theory existed, it cannot be supersymmetrised.…”
mentioning
confidence: 99%